A master's report in conducting for winds & percussion: analyses and rehearsal strategies for Sonata no. 13 by Giovanni Gabrieli, Serenade no. 12 in C minor by Wolfgang Amadeus Mozart, and Prelude, siciliano and rondo by Malcolm Arnold - Laney, Ryan Ray (Kansas State University, 2012)
This document was submitted to the Graduate School of Kansas State University as a partial requirement for the Master's in Music degree. It contains theoretical, historical, and rehearsal analyses for Sonata No. 13 by Giovanni Gabrieli as arranged for brass octet by Glenn Smith, movements II. Andante and III. Minuet & Trio from Serenade No. 12 in c minor by Wolfgang Amadeus Mozart as edited by Frederick Fennell, and Prelude, Siciliano and Rondo by Sir Malcolm Arnold as arranged for full symphonic band by John P. Paynter. Prelude, Siciliano and Rondo was performed by the Kansas State University Wind Ensemble on February 15, 2012 in McCain Auditorium on the Kansas State University campus. Sonata No. 13 was performed by members of the Kansas State University Brass Ensemble on April 18th, 2012 in McCain Auditorium. There was no formal performance or rehearsal for Serenade No. 12 in c minor. The analytical methods employed in this report include the Unit Study approach used in the Teaching Music Through Performance in Band book series and the Tracz method of macro-micro-macro graphical score analysis.
A master's report in conducting for winds and percussion
Keywords: Wind; Conducting; Music (0413); Music Education (0522)